2015
DOI: 10.1128/mbio.02236-14
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Tracking Reveals Antibiotic-Induced Changes in Mycobacterial Energy Metabolism

Abstract: ATP is a key molecule of cell physiology, but despite its importance, there are currently no methods for monitoring single-cell ATP fluctuations in live bacteria. This is a major obstacle in studies of bacterial energy metabolism, because there is a growing awareness that bacteria respond to stressors such as antibiotics in a highly individualistic manner. Here, we present a method for long-term single-cell tracking of ATP levels in Mycobacterium smegmatis based on a combination of microfluidics, time-lapse mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 47 publications
2
50
0
Order By: Relevance
“…In the light of the fact that many of the antimycobacterial drugs are linked to energy metabolism of Mtb (Black et al, 2014; Koul et al, 2014; Maglica et al, 2015), measuring the levels of the NADH:NAD + ratio becomes clinically important. Thus, we treated the Mtb Peredox with sub-lethal concentrations of antituberculosis agents for 6 and 24 h and calculated the NADH:NAD + ratio though CLSM analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In the light of the fact that many of the antimycobacterial drugs are linked to energy metabolism of Mtb (Black et al, 2014; Koul et al, 2014; Maglica et al, 2015), measuring the levels of the NADH:NAD + ratio becomes clinically important. Thus, we treated the Mtb Peredox with sub-lethal concentrations of antituberculosis agents for 6 and 24 h and calculated the NADH:NAD + ratio though CLSM analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In unicellular organisms, Maglica et al (2015) used ATeam sensors to monitor antibiotic induced cell death by single cell tracking of ATP levels in Mycobacterium smegmatis , demonstrating its potential as an important technology in drug discovery for antibiotic screening and mechanism of action imaging assays. In multicellular organisms, Ozawa et al (2015) found that glycolysis dependent ATP production was necessary for lamellipodia formation in podocytes.…”
Section: Methods For Detection and Imaging Atpmentioning
confidence: 99%
“…Targeted metabolomic studies have revealed significant changes in intracellular energy metabolites following antibiotic treatment [29-31], corroborated by live-cell imaging experiments directly measuring transient changes in ATP [32]. Experiments using the Seahorse XF Analyzer have captured real-time increases to cellular respiration by bactericidal antibiotics [33-35], complementing real-time measurements of overflow ROS production using electrochemical [36] or genetically encoded biosensors [33].…”
Section: Bactericidal Processesmentioning
confidence: 99%